Reduction of greenhouse gas emissions from agriculture in the light of international and EU climate protection law - Goździewicz-Biechońska, Justyna (Przegląd Prawa Rolnego, 2020)
The aim of the considerations was to reconstruct the system of international and EU climate protection law standards for the reduction of greenhouse gas emissions from agriculture and, consequently, to define the legal requirements for agriculture as a sector included in the reduction efforts carried out in this area. Currently, neither at the international nor at the EU level, is there a separate sector-specific regulation on this issue. However, this issue has been more and more frequently included in international agreements (with the Paris Agreement at the forefront), in strategic documents pertaining to the EU climate and energy policy, as well as in secondary EU legislation. The year 2020 is a crucial period in which the summaries and closures of reporting periods and the planning and building of new climate actions (especially within the European Green Deal) are taking place. This indicates the growing importance of climate regulations and their projected dynamic development, which also reflects an advancing ideological change regarding the potential of the agricultural sector in climate actions, particularly in respect of the reduction of greenhouse gas emissions from agriculture.